COMPARATIVE STUDY OF POLYMERIZATION DEPTH OF THREE PHOTOCOMPOSITE DENTAL FILLING MATERIALS FOR BULK FILL RESTORATION - Noenko, Igor; Pavlenko, Oleksiy; Mochalov, Iurii (Eastern Ukrainian Medical Journal, 2023)
The objectives of the study was to compare the depth of polymerization of flowable photocomposite dental restorative materials for bulk fill tooth restorations in laboratory.Materials and methods. Three flowable bulk fill photocomposite dental restorative materials – "SDR® Posterior Bulk Fill Flowable Base," "Filtek™ Bulk Fill Flowable" and domestic "Jen-Radiance Molar-FW" – were chosen for the study. For each material, 10 black opaque thin-walled polyvinyl chloride molds with a length of 10.00 mm and a diameter of 3.00 mm were prepared. The molds were air-dried from a compressor and fixed in fluoroplastic retainers perpendicular to the metal opaque surface below and subsequently filled with the investigated restorative material along the entire length, in a contact manner, along the wall. After filling, the material was polymerized with an LED photopolymerizer directly in contact with the surface of the light guide for 40 seconds. Subsequently, the material was removed from the forms and the remains of the unpolymerized mass were removed from the surface of the polymerized cylinder of the composite with a metal dental sickle-shaped carrier (scarification test). The length of the polymerized cylinder was measured using an electronic micrometer.Results. Therefore, the study of the depth of polymerization of flowable bulk fill photocomposites "SDR® Posterior Bulk Fill Flowable Base", "Filtek™ Bulk Fill Flowable" and domestic "Jen-Radiance Molar-FW" showed that signs of polymerization of all three materials were observed in a depth of more than the "declared" four millimeters which may be explained by the improvement of the recipe for the preparation of such materials and the optimization of the transparency of the organic component and inorganic filler, as well as the regular distribution of photoactivators in the mass. "SDR" polymerized to a depth of 7.38 ± 0.17 (M = 7.30) mm, the minimum value was 7.16 mm and the maximum value was 7.71 mm. "Filtek Bulk Fill Flowable" polymerized to a lesser depth – on 6.34 ± 0.14 (М = 6.38) mm, the minimum value was 6.05 mm and the maximum value was 6.55 mm. The domestic analogue "Jen-Radiance Molar‑FW" showed even higher values of polymerization depth – 8.03 ± 0.19 (М = 7.98) mm, the minimum value was equal to 7.75 mm and the maximum value was 8.41 mm. Statistical tests showed probable similarity between "SDR" and "Jen-Radiance Molar-FW" in the depth of polymerization.Conclusions. All three studied flowable bulk fill photocomposite materials were polymerized to a depth greater than 4.00 mm. Domestic "Jen-Radiance Molar-FW" was similar to "SDR" according to the investigated feature.